2019
DOI: 10.2478/fhort-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

A combination of biochar and regulated deficit irrigation improves tomato fruit quality: A comprehensive quality analysis

Abstract: Quality of fresh produce is the most critical issue in the economics of a vegetable enterprise. In order to investigate the effect of biochar amendment and deficit irrigation on tomato fruit quality, experimental research was conducted under a rain shelter in southern China during the 2017 and 2018 growing seasons. The experiment consisted of five treatments. Crops were irrigated to 100% of field water capacity at all growth stages as treatments T1 and T2. The other treatments received 30% less irrigation wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Some studies have reported that the amount of biochar also affects changes in soil microorganisms [8]. The tomato is rich in nutrients and is one of the most widely cultivated vegetables [9]. As an important economic crop, it is the main ingredient in some prepared food as well as a focus of the agricultural industry [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the amount of biochar also affects changes in soil microorganisms [8]. The tomato is rich in nutrients and is one of the most widely cultivated vegetables [9]. As an important economic crop, it is the main ingredient in some prepared food as well as a focus of the agricultural industry [10].…”
Section: Introductionmentioning
confidence: 99%
“…High soil degradation affects many cultivated areas worldwide [3] and changes in the water regime, especially due to longer drought periods [4], have caused this crop to be under great production stress. Biochar has shown to favor tomato crop performance with an increased yield production and weight under controlled deficit irrigation [5][6][7][8]. Particularly, bamboo biochar pyrolyzed at 300 ‱ C has had a significant positive effect on tomato quality and plant growth [9].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, bamboo biochar pyrolyzed at 300 ‱ C has had a significant positive effect on tomato quality and plant growth [9]. So far, studies like these have associated observed changes in fruit quality, yield to plant, and nutrient dynamics responses, but without investigating deeply the underlying soil physical mechanisms [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have proved that climate change could seriously affect the supply and demand for irrigation water owing to the continuous increase in temperature and atmospheric CO 2 levels that changed rainfall patterns and their distribution in recent years [ 18 , 19 ]. Innovative water-saving irrigation methods, such as deficit irrigation, were developed to address water scarcity and to improve water-use efficiency [ 20 ]. It is generally believed that water deficits will have a negative impact on yield and a positive impact on quality by increasing primary or secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%